Self-Concepts of Exercise in Frail Older Adults With Heart Failure: A Literature Review - Xie, Boqin; Arslanian-Engoren, Cynthia (Research and theory for nursing practice, 2015)
The co-occurrence of frailty and heart failure (HF) in older adults (65 years or older) can adversely affect the ability to engage in self-care management behaviors, which may alter self-concepts and decrease quality of life. Little is known about how frailty and HF influence older adults' self-concepts or how these self-concepts affect exercise behaviors. Therefore, the aims of this literature review were to identify the self-concepts of older frail adults with HF and to identify how these self-concepts affect their exercise behaviors. Guided by the schema model of self-concept, publications before April 2013 that examined the impact of the self-concepts of older adults with HF and/or frailty on exercise behavior were reviewed. As a result, 6 articles were included. Three of the 6 articles focused on frailty, and 3 of the 6 articles focused on HF. However, no study was found that specifically examined the self-concepts of frail older adults with HF. The self-concepts of older adults with HF and/or frailty are multifaceted and include both cognitive resources (facilitating exercise) and cognitive liabilities (hindering exercise). Studies are needed to determine how the co-occurrence of frailty and HF impact self-concepts and exercise behaviors in older adults.